Mayo Clinic Wellness Solutions for diabetes [videorecording (DVD)] (Mayo Clinic, 2007)
Physicians from the esteemed Mayo Clinic of Rochester, Minnesota provide male and female adult viewers with insights on the most effective means to cope with this condition. Sections include Integrative Medicine, Gentle Yoga, and Daily Nutrition.